Family Planning Practices, Knowledge, Decision Making, and Factors Associated with Unplanned Pregnancies among Women Working in A Selected Garment Industry in Urban Bengaluru, India - Hombaiah, Chandana (Populasi, 2024)
Background: According to UN population estimates, India has surpassed China as the world’s most populated nation, marking the biggest upheaval in global demography since records have been kept. Providing universal family planning services is an important strategy to reduce maternal morbidity and to control population growth. Even though the country has multiple programs addressing family planning issues, they are missing out on working women. Thus, this study aims to estimate the prevalence of unmet needs of family planning and determinants for improper access to family planning methods among women working in a selected Garment industry in Urban Bengaluru. Methodology: A community based cross-sectional study was conducted in a selected garment factory for a period of two months. Women workers in Reproductive age group (18-49 years) and who gave voluntary consent to participate in the study were taken up. Total sample of 454 women were included. The data was collected using a semi-structured and validated questionnaire. Collected data was entered in Microsoft Excel and was analysed using SPSS version 16. Results: Among 454 participants, 42.3% (n=192) of them had used contraceptive method. Out of 192 women, most of them (72.9%, n=140) had chosen tubectomy as the contraceptive measure. Among 407 women, 14.3% (n=58), 13.3% (n=42), and 20.9% (n=9) of them had not planned for their 1st pregnancy, 2nd pregnancy, and 3rd pregnancy respectively. Conclusion: Less than half of them had used any form of contraceptive method. Among that half, nearly three-fourths had chosen tubectomy.